2006
DOI: 10.1017/s1355617707070051
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cognitive change over time and relationship to age following successful treatment of Cushing's disease

Abstract: Chronically elevated levels of cortisol have been associated with changes in cognitive functioning and brain morphology. Using Cushing's disease as a model to assess the effects of high levels of cortisol on cognitive functioning, 27 patients with Cushing's disease were examined at baseline and three successive follow-up periods up to 18 months after successful surgical treatment. At all follow-up periods, patients were administered cognitive tests as well as measures of plasma and urinary free cortisol. Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 35 publications
5
51
0
Order By: Relevance
“…Prior studies have looked at cognitive and hippocampal volume changes in patients with Cushing's disease before and after treatment of the hypercortisolemia. Adults with Cushing's disease demonstrate improvement in some, but not all, cognitive domains following normalization of cortisol levels (Hook et al, 2007). An increase in hippocampal volume of approximately 3% is reported 17 months after surgical excision of the ACTHsecreting tumor in patients with Cushing's disease (Starkman et al, 1999(Starkman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have looked at cognitive and hippocampal volume changes in patients with Cushing's disease before and after treatment of the hypercortisolemia. Adults with Cushing's disease demonstrate improvement in some, but not all, cognitive domains following normalization of cortisol levels (Hook et al, 2007). An increase in hippocampal volume of approximately 3% is reported 17 months after surgical excision of the ACTHsecreting tumor in patients with Cushing's disease (Starkman et al, 1999(Starkman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Bourdeau et al (15) found no correlation between brain volume and current age, although this could be related to the relatively young sample of patients included. An increase in hippocampal volume was associated with a decrease in UFC after treatment (12,13,21), but not with reduction in plasma cortisol, duration of disease, or the number of months relapsed since treatment (21,30). Increase in right caudate head volume (CHV) was also associated with decrease in UFC, while increase in left CHV and right and left CHV together were not associated with change in UFC (13,21).…”
Section: Associations Between Brain Abnormalities and Clinical Characmentioning
confidence: 96%
“…In adolescents with active CS, left amygdala activation and right anterior hippocampal activation did not correlate with the performance of a facial memory task (26). Increase in hippocampal volume after correction of hypercortisolism was positively associated with improvement in learning (13,30), but change in CHV was not (13,30). An increase in right caudate volume was associated with improvement in mood (depression and anxiety) and related ideation (obsessive-compulsive and paranoid ideation), whereas change in left CHV and hippocampal volume were not correlated with mood or ideation (21).…”
Section: Associations Between Brain Abnormalities and Behavioral Outcmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, prolonged cortisol elevations predict memory dysfunction and reduced volume of the hippocampus and ACC during aging (9,10). Moreover, in patients with Cushing's syndrome, hypercortisolism was associated with smaller hippocampal volumes and overall brain atrophy (11,12,13), with increasing hippocampal volumes and improving emotional and cognitive functioning after correction of hypercortisolism (11,14,15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%